Infinite-dimensional Sylvester equations: basic theory and application to observer design - Emirsajłow, Zbigniew (Zielona Góra: Uniwersytet Zielonogórski)
This paper develops a mathematical framework for the infinite-dimensional Sylvester equation both in the differential and the algebraic form. It uses the implemented semigroup concept as the main mathematical tool. This concept may be found in the literature on evolution equations occurring in mathematics and physics and is rather unknown in systems and control theories
Keywords: infinite-dimensional Sylvester equation; implemented semigroup; state observer design